High-performance active power filter implementation based on predictive current control - Bachar Rahima; Golea Amar; Benchouia Mohamed Toufik; Chebaani Mohamed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper presents the use of the predictive strategy concept to improve the Active Power Filter (APF) performance, by compensation of the reactive power and elimination of the harmonic currents generated by non-linear loads. Predictive control is generating considerable interest when it comes to implementing current control strategies in active power filter. The proposed strategy provides a simple controller incorporating Phase Locked Loop (PLL) independency. The prediction is evaluated using a cost function that quantiﬁes the desired system behavior. The cost function used in this work evaluates the ﬁltered error of the currents. This strategy minimized the number of sensors, ease of practical implementation and reduced system size and cost. The effectiveness of the proposed controller is confirmed through simulation and experimental validation using a hardware prototype based on dSPACE-1104